2010
DOI: 10.1007/s00464-010-0968-3
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal natural orifice translumenal endoscopic surgery (NOTES): a survey of women’s views on a new technique

Abstract: Potentially, NOTES surgery offers women a scarless operation with the possibility of less pain than experienced in standard laparoscopic surgery. Few women, however, were troubled about the cosmetic effect of surgery. The effect of NOTES on sexual function was expressed as a particular concern by younger women. In all groups and across all ages, peritoneal access using the transvaginal route was met by significant scepticism. In Australia, women remain to be convinced about the potential advantages of the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 18 publications
3
44
1
4
Order By: Relevance
“…On the other hand, the safety profile of surgical procedures was considered to be of vital importance; in our sample, the risk of complications was considered the most important aspect of a surgical procedure by nearly 90% of patients. This result is in line with other published surveys [7,8,21,22]. In a recent paper [23] on 420 subjects, the most important concern regarding surgical therapy was the fear of surgical complication, with 92% placing it first, whereas postoperative scars were the first concern for only 2% of the participants.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, the safety profile of surgical procedures was considered to be of vital importance; in our sample, the risk of complications was considered the most important aspect of a surgical procedure by nearly 90% of patients. This result is in line with other published surveys [7,8,21,22]. In a recent paper [23] on 420 subjects, the most important concern regarding surgical therapy was the fear of surgical complication, with 92% placing it first, whereas postoperative scars were the first concern for only 2% of the participants.…”
Section: Discussionsupporting
confidence: 79%
“…Peterson et al [8] reported that in 100 women asked for NOTES cholecystectomy 73% would consider a trans-vaginal procedure, and 68% indicated that if the data show equivalency between laparoscopic and trans-vaginal procedures, they would prefer the latter approach. On the other hand, in another recent paper [22], observational data from 300 women revealed that 75% were indifferent or sceptical towards the NOTES technique for cholecystectomy, even if the two approaches (NOTES and laparoscopy) were defined as similar in outcome. In Rao et al [9], a hypothetical scenario was given in which the respondent presents as an emergency in a hospital requiring an appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, three-fourths of the women surveyed were neutral or unhappy about the prospect of a NOTES procedure, even it was stipulated that laparoscopy and NOTES had equivalent safety and efficacy. The effect of NOTES on sexual function was expressed as a particular concern by younger women [76]. In another report, Peterson et al surveyed 100 women, exploring their concerns and opinions regarding transvaginal surgery [77].…”
Section: 4mentioning
confidence: 99%
“…Postoperative intercourse abstinence after transvaginal NOTES elicited worry in 76% of responders. As previously reported, 18 concerns related to sexual function and fertility must be taken into account when dealing with a female population.…”
Section: Notes Versus Less: Comparative Analysismentioning
confidence: 99%
“…18 In their study, 300 individuals were surveyed, including 195 health professionals, 37 patients who were undergoing or had recently undergone laparoscopic cholecystectomy, and 68 gynecologic clinic patients. The results suggested that the compelling incentive for NOTES, namely the absence of abdominal scars, might not be such an important factor for many patients.…”
Section: Comment Which Patients Would Prefer Notes and Why?mentioning
confidence: 99%